Employers’ perceived attitude towards hiring disabled persons and an investigation into the barrier-free environment at workplace in Selangor and Federal Territory / Zamalia Mahmud and Rosli Abdul Rahim - Mahmud, Zamalia; Abdul Rahim, Rosli (Universiti Teknologi MARA, Shah Alam, 2009)
Employment of disabled persons is an issue in the employment practices of many corporations and organizations. It is acknowledged that disabled persons find it more difficult to be employed compared to persons with no disabilities. Thus this study sets out to investigate the practices in the employment of the disabled by business corporations in Malaysia, mainly the attitude of employers towards hiring disabled persons from the aspect of dependability, productivity and acceptance towards the disabled. This study has found that slightly more than fifty percent of the corporations surveyed do not hire disabled persons. Among the reasons given by the employers include communication difficulties, disabled persons deemed not efficient as compared to able employees, unsuitable nature of work and higher cost incurred by organization. In general, employers of the private limited corporations tend to be slightly more positive in their attitude and willingness to hire disabled persons compared to the employers of the public listed corporations. These include their willingness to motivate and assist disabled persons with their employment. On a general scale, majority of the employers in public listed corporations have less than positive attitude towards hiring disabled persons for various reasons which are described in this study.